Applying the Learning Multimedia Applications for Completion of Linear Equations with Subscription Methods - Simarmata, Janner; Napitupulu, Efendi; Tambunan, ARS; ., Murdani; Barita Nauli Simangunsong, Pandi; Rikki, Alex; Jean Cross Sihombing, Denny; Limbong, Tonni; DP Silitonga, Parasian; Purba, esinta; Paul Harianja, Andy; Pakpahan, Sorang; et al. (International Journal of Engineering and Technology, 2018)
The progress of communication and information technology needs to continuously adapt to various disciplines where one of them is education. This progress will undoubtedly give hope for changes in the learning process that is getting better by using multiple approaches to strategies, methods, teaching materials and media as well as assessment systems in learning, including in solving linear equations. The main problem that arises in solving linear equations in schools is the low ability of students to count and the learning system; this is because the learning conducted in schools is still using the books as media. Learning systems of linear equations usually taught through books seem very saturating. The teachers are necessary to design an exciting and interactive learning application to explain the linear equations system. Therefore to support the learning needs to be developed informative and creative learning applications so that it is easy to learn. Computer Assisted Instruction (CAI) is a method of vocational training approaches whose primary emphasis is on what a person can do as a result of training. It is hoped that this learning application can help students understand and increase students' enthusiasm and motivation to learn the two-variable linear equations system.Â Â